Exploring the Influence of Parenting Styles on State and Trait Anxiety among University Students: A Comparative Analysis - Dr. ERUM MOOSA,; Dr. AZRA SHAHEEN, (Al-Qanṭara, 2024)
An individual’s personality and traits are shaped by childhood experiences and parenting styles. Findings suggest that young adults experiencing severe anxiety have generally experienced varying levels of comfort, freedom, and feedback characterized by different parenting styles (Krohne, 1980). Since young adults are undergoing a critical transition in their university life, their susceptibility to anxiety i.e., state and trait is elevated reported by many studies. Consequently, the current research aims to study the relationship between parenting styles and trait and state anxiety in university students. It is a quantitative correlational study where data was collected from 200 university going students through convenience sampling. The Parental Authoritative Questionnaire (PAQ) and State-Trait Anxiety Inventory Scale (STAI) were employed to study the variables. The data analysis was done through SPSS 22 and Pearson correlation and T-Test were calculated. The results indicated a positive correlation between authoritarian and permissive parenting style with state and trait anxiety and a negative correlation between authoritative parenting style with state and trait anxiety. A significant difference was found between the state anxiety of male and female students. The three subscales of the father’s parenting style indicated a substantial difference however no significant difference was indicated between the mother’s parenting styles. Therefore, it was observed that parenting style has a considerable impact on both state and trait anxiety in university students.